PRAANGGAPAN DALAM PIDATO OBAMA PADA APEC CEO SUMMIT 2014 - DWI PEBRINA SINAGA; NURUL HUSNAH HARAHAP (LP2MTBM MAKARIOZ, 2020)
The title of this study is Preconcession in Obama's Speech at the 2014 APEC CEO Summit. Speech is one of the politicallanguage that is very considered by not only politicians but also the lay people, because in it there is an opinion ordescription of an important thing and worth discussing. Not a little implied meaning is contained in each speaker's speech,and therefore presumpation is considered a good tool for knowing the basis of the speaker's speech. The preconceivednessthat appeared in Obama's speech was 26 with five types of presumptions emerging, namely an existential preconceivednessof 34.6%, followed by a lexical presumpation of 23.1%, an active presumpation of 19.2%, a non-active response of 15.4%,and a factual counter presumpion of 7.7%. Through existential, factive, off-factive, and factual presumption, it is well knownthat Obama is eager to establish bilateral cooperation with China better in business and investment than with other countries.